Double Island Slip Flap for Reconstruction of Surgical Defects of the Upper Lip - Ferraz,Pedro Dias (2021)
ABSTRACT The double V-Y sliding island flap is a viable option for the reconstruction of lip defects, with a favorable cosmetic-functional result. We present the case of a woman with a basal cell carcinoma of the upper labial region, that after excision, has been reconstructed using a double sliding island flap. The authors describe the surgical technique as well as its main advantages and applicability.